Ultrasonic Studies on the Molecular Interaction of Ethyl Cellulose in n-Alkanols - Raju, K.; Rakkappan, C. (Asian Journal of Chemistry, 2010)
Ultrasonic velocity, viscosity and density for the solutions of ethyl cellulose in propan-1-ol, butan-1-ol, pentan-1-ol and hexan-1-ol mixtures were measured at 303, 313 and 323 K. From the experimental data, the various acoustical parameters such as adiabatic compressibility (bad), Rao number (R), free length (Lf), internal pressure (pi) and solvation number (Sn) have been computed. The trends in acoustical parameters indicate that there are molecular interactions between the components.